Transcriptional Dysregulation in NIPBL and Cohesin Mutant Human Cells - Liu, Jinglan; Zhang, Zhe; Bando, Masashige; Itoh, Takehiko; Deardorff, Matthew A.; Clark, Dinah; Kaur, Maninder; Tandy, Stephany; Kondoh, Tatsuro; Rappaport, Eric; Spinner, Nancy B.; Vega, Hugo; et al. (PLoS biology, 2009)
Cohesin regulates sister chromatid cohesion during the mitotic cell cycle with Nipped-B-Like (NIPBL) facilitating its loading and unloading. In addition to this canonical role, cohesin has also been demonstrated to play a critical role in regulation of gene expression in nondividing cells. Heterozygous mutations in the cohesin regulator NIPBL or cohesin structural components SMC1A and SMC3 result in the multisystem developmental disorder Cornelia de Lange Syndrome (CdLS). Genome-wide assessment of transcription in 16 mutant cell lines from severely affected CdLS probands has identified a unique profile of dysregulated gene expression that was validated in an additional 101 samples and correlates with phenotypic severity. This profile could serve as a diagnostic and classification tool. Cohesin binding analysis demonstrates a preference for intergenic regions suggesting a cis-regulatory function mimicking that of a boundary/insulator interacting protein. However, the binding sites are enriched within the promoter regions of the dysregulated genes and are significantly decreased in CdLS proband, indicating an alternative role of cohesin as a transcription factor.